A method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate

Through the separation-catalytic sequence structure ultrafiltration membrane of electrospinned nanofiber substrates, macromolecular substances are separated first and then catalytic treatment is carried out, which solves the problem of macromolecular interference in advanced oxidation, and achieves efficient removal and catalytic of composite micropollutants. The protection of materials improves water treatment efficiency and resource utilization efficiency.

CN114345139BActive Publication Date: 2024-12-17NANJING UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202210095872.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-26
Publication Date
2024-12-17
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

Existing water treatment technologies are difficult to effectively remove composite micropollutants, especially during advanced oxidation, where macromolecular organic matter in industrial wastewater interferes with catalytic materials, resulting in a degradation performance of small-molecular pollutants.

Method used

Using electrospun nanofiber as the substrate for separation-catalytic sequence ultrafiltration membrane, through the combination of nanocatalytic materials and polymers, the macromolecular substances are first separated, and then catalytic treatment is carried out to protect the catalytic materials and enhance the degradation of small-molecular pollutants. efficiency.

Benefits of technology

It realizes efficient removal of multi-component pollutants, protects catalytic materials, shortens treatment processes, reduces energy consumption and floor area, and avoids the loss and difficulty in recycling of catalytic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004897002960000011
    Figure HDA0004897002960000011
  • Figure HDA0004897002960000012
    Figure HDA0004897002960000012
  • Figure HDA0004897002960000013
    Figure HDA0004897002960000013
Patent Text Reader

Abstract

The present invention discloses a method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate. The method uses a nanofiber membrane doped with nanoparticles prepared by electrospinning as a substrate, synthesizes an ultrafiltration membrane thereon by a non-solvent induced phase separation method, and obtains a multifunctional membrane with a separation-catalysis spatial order. The membrane successfully integrates separation and catalysis into a functionalized molecular sieve membrane, which not only maintains the original high flux and high retention of the ultrafiltration membrane, but also can select suitable nanomaterial electrospun nanofibers as a base catalytic layer according to different pollutants, thereby achieving efficient degradation of pollutants. The removal of multi-component pollutants mainly depends on the orderly arrangement of separation and catalysis. Membrane separation removes macromolecular substances such as natural organic matter that affect the advanced oxidation process before catalysis, thereby improving the degradation performance of the catalytic layer for small molecules; at the same time, the confinement effect of the spinning fiber on the catalyst effectively solves the problem of nanoparticle loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of advanced oxidation and membrane separation materials, in particular to a method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate. Background Art

[0002] With the rapid economic development and the continuous growth of population, the demand for water resources is increasing. Natural water bodies are often unable to be used by humans due to pollution. Wastewater resource utilization is considered to be an effective means to solve the shortage of water resources. Among them, the double membrane process with "microfiltration / ultrafiltration + reverse osmosis" as the core technology is the main water reuse technology. However, in the process of chemical wastewater reuse and treatment, there are many types of pollutants, diverse physical and chemical properties, wide concentration distribution, complex occurrence forms, and mutual influence between components, which leads to increased difficulty in treatment. Although the advanced oxidation process makes the treatment of characteristic pollutants in multi-component wastewater efficient and fast, in the actual water treatment process, the advanced oxidation process is easily affected by complex water quality. Macromolecular organic matter such as natural organic matter in the secondary effluent of industrial wastewater will compete with active oxygen species and adsorb and occupy the active sites of catalytic materials, resulting in the degradation of small molecular characteristic pollutants such as phenols. The existing water treatment technology is difficult to effectively solve the problem, so we urgently need to develop a new type of synergistic coupling treatment technology to meet the efficient removal of complex micropollutants.

[0003] Membrane separation and catalytic coupling process is a cutting-edge and efficient water reuse technology. Through the study of the physical and chemical properties of pollutants, the design of new membrane materials with separation-catalysis spatial order is a hot process. Through membrane separation, the interference of macromolecular substances on advanced oxidation processes is shielded, and the catalytic materials are protected to enhance the degradation and conversion of small molecular micropollutants, and the removal efficiency of complex micropollutants is improved simultaneously. At the same time, the replacement of the membrane substrate can realize the large-scale preparation of new coupling membranes. In addition, the membrane separation and catalytic coupling process is of great significance for shortening the process, reducing the floor space, and reducing energy consumption in industrial processing. Summary of the invention

[0004] The invention relates to a method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate is completed by the following steps:

[0007] Step 1: Electrospinning nanofiber membrane; Weigh a certain amount of nanomaterial powder and ultrasonically disperse it in N,N-dimethylformamide (DMF) solution for 1 hour. After uniform dispersion, add a certain proportion of polyacrylonitrile (PAN) and polyvinyl pyrrolidone K30 (PVP) and seal it. Heat and stir in a 60℃ water bath for 2 hours to obtain a spinning solution with moderate viscosity and uniform dispersion; Pour the prepared spinning solution into a syringe and electrospin it in an electrospinning machine to obtain a nanofiber membrane;

[0008] Step 2: Prepare PES ultrafiltration membrane by phase inversion method; first, dissolve polyethersulfone (PES) and polyethylene glycol (PEG) in DMF; the mixture is stirred at 60°C for 8 hours until a uniform and transparent polymer solution is formed; the prepared casting solution is allowed to stand at room temperature for 12 hours for degassing. After the electrospun nanofiber membrane is evenly spread on the glass plate, the casting solution is evenly coated on the surface of the nanofiber with a 450μm scraper. After staying in the air for 5 seconds, the glass plate is immediately placed in deionized water to induce phase inversion; the formed PES ultrafiltration membrane is soaked in a gel bath for 15 minutes and then transferred to deionized water for overnight storage to ensure complete phase inversion and solvent elution.

[0009] In the above steps, the substrate of the membrane material is an electrospun nanofiber with catalytic / adsorbent function loaded with nanocatalytic material / nanoadsorbent material;

[0010] In the above step 1, the mass fraction of PAN is 6-11%, the mass fraction of nanomaterials is 7-10%, and the mass fraction of PVP is 3-6%;

[0011] In the above step 1, the nanomaterial is selected according to the needs;

[0012] In the above step 1, the positive pressure of the electrospinning voltage is set to 10-15 kV, the negative pressure is set to 1-3 kV, and the injection rate is set to 0.08-0.1 mm / min;

[0013] In the above step 1, the humidity of the electrospinning environment is controlled at 10-30%, and the temperature is controlled at 30-50°C;

[0014] In the above step 2, the mass fraction of PES is 15.5-16.5%, and the mass fraction of PEG is 8-9%.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] (1) The material realizes a spatial structure of separation first and then catalysis, which can intercept macromolecular substances in advance for multi-component pollutants, pre-treat them for subsequent catalysis, and ensure the efficient operation of the advanced oxidation process;

[0017] (2) Nanofibers have a limited effect on the catalytic material, solving the problem of easy loss and difficulty in recycling of catalytic materials;

[0018] (3) The thickness of the nanofiber support layer can be freely selected. By adding PVP, the exposure of the active sites of the catalytic material can be increased, thus maintaining a high catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Actual pictures of the front and bottom surfaces of the multifunctional ultrafiltration membrane prepared in Example 1 of the present invention.

[0020] Figure 2 The SEM images of the multifunctional ultrafiltration membrane prepared in Example 1 of the present invention are: (a) cross section, (b) front separation layer surface, (c) bottom surface (nanofibers), (d) nanofibers at high magnification, and (e) nanocatalytic material after carbonization.

[0021] Figure 3 The retention performance of the multifunctional ultrafiltration membrane of Example 1 of the present invention for bovine serum albumin (BSA) and humic acid (HA) is shown.

[0022] Figure 4 This is a comparison of the removal performance of the nanofiber membrane substrate of Example 1 of the present invention for BPA and BPA+HA mixed system (different fluxes).

[0023] Figure 5 The removal performance of the multifunctional ultrafiltration membrane of Example 1 of the present invention for BPA at different fluxes (different residence times).

[0024] Figure 6 The removal performance of the multifunctional ultrafiltration membrane of Example 1 of the present invention placed forward (UFC) and the comparative example 1 placed reversely (CFU) for multi-component pollutants in a complex system is shown. DETAILED DESCRIPTION

[0025] The present invention will be described below in conjunction with the accompanying drawings.

[0026] The present invention utilizes nanofibers with catalytic properties to replace conventional non-woven fabrics as membrane substrates, thereby providing mechanical support for the polymer ultrafiltration membrane and giving the membrane material an efficient catalytic function, thereby obtaining a multifunctional ultrafiltration membrane with a separation-catalysis spatial order. Based on the orderly arrangement of ultrafiltration and catalysis, it can synergistically remove a variety of pollutants in complex water matrices, thereby achieving efficient water purification and water reuse.

[0027] Example 1

[0028] This example is a material preparation experiment.

[0029] Step 1: Electrospinning nanofiber membrane: 15 g Co(NO3 ) 2 6H 2 O to make solution 1, add 70g 2-methylimidazole to 250mL deionized water to make solution 2; under stirring conditions, mix the above two solutions, stir vigorously for 10min, stand at room temperature for 24h, and separate by centrifugation at 8000rpm for 15min; the sample obtained after drying is carbonized at 200-800℃ under the protection of non-oxidizing gas; and C-ZIF-67 nanocatalyst is prepared. Weigh 0.6g C-ZIF-67 powder in 5.5mL DMF solution for ultrasonic dispersion for 1h, add 0.4g PAN and 0.4g PVP after uniform dispersion, and seal. Heat and stir in a 60℃ water bath for 2h to obtain a spinning solution with moderate viscosity and uniform dispersion; inject the prepared spinning solution into a 5mL syringe, and use electrospinning technology with a positive pressure of 10kV, a negative pressure of 2kV, and a push rate of 0.08mm / min to obtain a nanofiber membrane;

[0030] Step 2: Prepare PES ultrafiltration membrane by phase inversion method; First, add 31.142g of dried PES and 15.099g of PEG to 150mL of DMF; The mixture is stirred at 60℃ for 8h until a uniform and transparent polymer solution is formed; The prepared casting solution is allowed to stand at room temperature for 12h for degassing. After the nanofiber membrane is evenly spread on the glass plate, the casting solution is evenly coated on the surface of the nanofiber with a 450μm scraper. After staying in the air for 5s, the glass plate is immediately placed in deionized water to induce phase inversion; The formed PES ultrafiltration membrane is soaked in a gel bath for 15min and then transferred to deionized water for overnight storage to ensure complete phase inversion and solvent elution.

[0031] This example is an application test, in which the multifunctional ultrafiltration membrane prepared in Example 1 is forward installed (UFC) into a homemade membrane filtration device.

[0032] Model pollutants, including small molecule bisphenol A (BPA) and large molecule humic acid (HA), were dissolved in water to prepare stock solutions. A mixed solution A containing 5ppm BPA and 25ppm HA or a 5ppm BPA solution B was prepared. 0.1g persulfate (PMS) was dissolved in solution A or solution B ([BPA] = 1ppm, [HA] = 5ppm, [PMS] = 0.1g / L, HA was added as an option), and the pollutant removal performance of the multifunctional ultrafiltration membrane UFC and the nanofiber layer at different fluxes, as well as the pollutant removal performance under different systems, was tested.

[0033] Comparative Example 1

[0034] This example is an application test, in which the multifunctional ultrafiltration membrane (UFC) prepared in Example 1 is reversely installed in a self-made membrane filtration device, named CUF.

[0035] Figure 2 a It can be seen that a multifunctional ultrafiltration membrane with a thickness of about 400 μm was prepared, in which the nanofiber layer was 55 μm thick and the traditional ultrafiltration membrane layer was about 350 μm thick. The ultrafiltration membrane support layer and the nanofiber layer were closely connected, and the dense separation layer and the porous support layer structure remained intact. It can be seen that the ultrafiltration membrane structure was not adversely affected by the change of the substrate. During the phase separation process on the nanofiber surface, the casting liquid of the ultrafiltration membrane will partially penetrate into the pores of the nanofiber membrane and cover the surface of the fiber at the same time, so that the separation layer and the catalytic layer are closely combined through physical action; at the same time, through the addition of polyethylene glycol and polyvinyl pyrrolidone, many pores are generated between the ultrafiltration membrane support layer and the nanofiber surface. When the casting liquid covers the fiber surface, these pores maintain the exposure of the active sites of the nanomaterial, thereby ensuring that the feed liquid and the active sites of the nanocatalytic material are effectively in contact, and maintaining the efficient catalytic performance of the catalytic material. When polyethylene glycol and polyvinyl pyrrolidone are not doped, the nanomaterials are tightly wrapped by the polymers and most of the active sites are covered, resulting in a decrease in the amount of free radicals produced, thereby reducing the catalytic performance. Figure 2 As can be seen from the cde diagram, the nanocatalytic material with a particle size of 950nm was synthesized after carbonization, and electrospinning made it evenly dispersed in the fiber, which confined it and avoided the loss and difficulty of recycling the catalytic material. Figure 2 b It can be seen that the pores on the surface of the ultrafiltration membrane are evenly distributed, and the pore size is mainly distributed in 10-20nm. This method perfectly forms a multifunctional ultrafiltration membrane with a separation-catalysis spatial order structure.

[0036] Figure 3 The separation efficiency of the multifunctional ultrafiltration membrane in Example 1 of the present invention for macromolecular pollutants is 97.04% for bovine serum albumin and 95% for humic acid.

[0037] Figure 4 It was shown that when only the nanofiber catalytic layer was used, at the same pure water flux, the presence of HA greatly reduced the removal efficiency of BPA by the nanocatalytic material, which indicated that HA had a greater negative impact on the advanced oxidation process in the complex pollutant system where HA existed.

[0038] Figure 5 The removal performance of BPA by the UFC membrane in Example 1 of the present invention is shown in Figure 1. It can be seen that even at a very high flux, the removal effect of BPA can still be guaranteed. As the flux increases, the removal rate of BPA decreases. This is because the increase in flux causes the pollutants to have insufficient residence time in the membrane and shorten the reaction time. Figure 4It can be seen that when the flux increases, the BPA removal efficiency of the UFC membrane decreases more slowly than when only the nanofiber layer exists. This is because under low pressure, the support layer of the ultrafiltration membrane has a certain decompression effect on the catalytic layer, which can cut the water flow, disperse the pressure, maintain the thickness of the catalytic layer, and extend the hydraulic retention time.

[0039] Figure 6 The BPA removal performance of UFC and CUF in Example 1 and Comparative Example 1 is compared for the mixed liquid of BPA and HA. In the homemade filtration device, 1 cm 2 The membrane was used to filter 300 mL of mixed liquid in a dead-end filtration device. The BPA degradation efficiency of the CUF membrane dropped rapidly compared to that of the UFC. This is because the selective layer in the UFC mode faces the inlet side. HA is pre-removed under the separation effect of the membrane. HA is retained on the surface of the ultrafiltration membrane separation layer and cannot contact the catalytic layer at the bottom, achieving its pre-removal and gradient separation of pollutants. As a result, HA has a smaller negative impact on the degradation performance, and disinfection by-products using it as a precursor cannot be generated. When there is no pre-separation effect of the membrane, HA will compete with active oxygen species, resulting in a decrease in the degradation efficiency of BPA. This multifunctional membrane with a separation-catalysis spatial structure has great potential for multi-component chemical wastewater treatment and provides a reliable technical means for drinking water purification and wastewater resource utilization.

Claims

1. A method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate, characterized in that: The following steps are involved: Step 1: Prepare nanofiber membrane; weigh a certain amount of nanomaterial powder and ultrasonically disperse it in N,N-dimethylformamide solution for 1 hour, add a certain proportion of polyacrylonitrile and polyvinylpyrrolidone K30 after uniform dispersion, and seal; heat and stir in a 60°C water bath for 2 hours to obtain a spinning solution with moderate viscosity and uniform mixing; pour the prepared spinning solution into a syringe, and electrospin in an electrospinning machine to obtain a nanofiber membrane; Step 2: Prepare polyethersulfone ultrafiltration membrane by phase inversion method; first, dissolve polyethersulfone and polyethylene glycol in N,N-dimethylformamide solution; the mixture is continuously stirred at 60°C for 8 hours until a uniform and transparent polymer solution is formed; the prepared casting solution is allowed to stand and degas for 12 hours at room temperature; the electrospun nanofiber membrane is spread evenly on a glass plate, and then the casting solution is evenly coated on the surface of the nanofiber with a 450μm scraper. After staying in the air for 5 seconds, the glass plate is immediately placed in deionized water to induce phase inversion; the formed polyethersulfone ultrafiltration membrane is soaked in a gel bath for 15 minutes and then transferred to deionized water for overnight storage to ensure complete phase inversion and solvent elution.

2. The method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate according to claim 1, characterized in that: The substrate of the membrane material is electrospun nanofibers loaded with nanocatalytic materials / nanoadsorbent materials and having catalytic / adsorbent functions.

3. The method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate according to claim 1, characterized in that: In step 1, the mass fraction of polyacrylonitrile is 6-11%, the mass fraction of nanomaterial is 7-10%, and the mass fraction of polyvinyl pyrrolidone K30 is 3-6%.

4. The method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate according to claim 1, characterized in that: In step 1, nanomaterials are selected according to needs.

5. The method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate according to claim 1, characterized in that: In step 1, the positive pressure of the electrospinning voltage is set to 10-15 kV, the negative pressure is set to 1-3 kV, and the injection rate is set to 0.08-0.1 mm / min.

6. The method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate according to claim 1, characterized in that: In step 1, the humidity of the electrospinning environment is controlled at 10-30%, and the temperature is controlled at 30-50°C.

7. The method for preparing a separation-catalysis structured ultrafiltration membrane using electrospun nanofibers as a substrate according to claim 1, characterized in that: In step 2, the mass fraction of polyethersulfone is 15.5-16.5%, and the mass fraction of polyethylene glycol is 8-9%.

Citation Information

Cited By

  • Composite membrane with functions of adsorption separation and catalytic degradation of new pollutants as well as preparation method and application of composite membrane

    CN121911246A

  • A composite membrane with adsorption separation-catalytic degradation of new pollutants and a preparation method and application thereof

    CN121911246B